Evaluación de una técnica bilaminar para cubrir recesiones gingivales. Resultados preliminares (2005)
ABSTRACT: The purpose of this study was to evaluate, over a six month period, the reduction of gingival recession using a bilaminar technique employing a sub-epithelial free connective tissue graft placed under a coronally advanced partial-thickness pedicle flap. 19 buccal recession defects in 6 patients were treated using this technique. The measurements of the amount of gingival recession (GR) and clinical attachment loss (CAL) were performed before surgery, and 1, 3, 6 months after surgery. Descriptive statistics was expressed with means and standard deviation. Longitudinal variations were evaluated with variance analysis. GR decreased, corresponding to 89.4% in average of root coverage the first month after surgery and 78.% in average at sixth months after surgery of root coverage. CAL decreased 0.96 mm. These results indicate that the bilaminar technique employing a connective tissue graft with partial thickness coronal advancement pedicle is a predictable method for root coverage and the clinical outcomes gained by this technique can be well maintained.